The execution of the Direct Money Program in school in the municipality of Guarapari, Espírito Santo (Research, Society and Development, 2022)
The Right to Education is a fundamental right and must be observed. In this context, regardless of governmental ideologies, it is necessary public policies that include the school management of national public schools in all its aspects, from infrastructure to pedagogical and evaluative ones. Aiming at the decentralization of financial resources, the exercise of citizenship and the autonomy of public schools, the Dinheiro Direto na Escola Program (PDDE) was created. From this perspective, the municipality of Guarapari has stood out in the observance of legislation at the state and national level. The present study aimed to detail the PDDE and highlight the management of the municipality of Guarapari. To this end, an exploratory and descriptive bibliographic research was used, in databases such as Scielo, including laws, regulations and decrees, as well as documents from the municipal government of Guarapari, ES. The results and the discussions carried out were described in textual production, with two distinct but complementary subtitles, which are: Programa Dinheiro Direto na Escola (PDDE); The execution of the PDDE in the municipality of Guarapari. The author's conclusions and personal impressions are in the final considerations.